Magnetic mineralogy of Variscan granites from northern Portugal: an approach to their petrogenesis and metallogenic potential - C. Cruz; H. Sant'Ovaia; F. Noronha (Geologica Acta, 2020)
Northern Portugal is characterized by the occurrence of numerous W hydrothermal deposits spatially associated with granites. The primary goal of this work is to establish a relationship between the magnetic behavior of the granites and the redox conditions during magma genesis, as this can influence the occurrence of mineralizations, namely of W (Mo). To this end, the magnetic mineralogy of the granites of the Lamas de Olo Pluton, a posttectonic pluton in northern Portugal, with associated W (Mo) occurrences was characterized and compared with the magnetic mineralogy of other post-tectonic Variscan plutons. This pluton is composed of different biotite granites: Lamas de Olo, Alto dos Cabeços and Barragem. To better characterize its magnetic behavior, different analytical techniques that complement previous magnetic susceptibility studies were performed. The magnetic mineralogy of Lamas de Olo Pluton was then compared with other post-tectonic Variscan plutons such as the Vila Pouca de Aguiar, Peneda-Gerês and Lavadores-Madalena plutons. The presence of magnetite in some of these granites is important because it points to melt-oxidized conditions not commonly found in Iberian Variscan granites. Our study shows that granite areas where magnetite and/or magnetite/ilmenite coexist are important targets for W (Mo) mineralizations. The results indicate that a few plutons have granites with a complex redox history which leads to the formation of magnetite and ilmenite.